Vegetation structure influences predation rates of early nests in subarctic breeding waders. (3rd April 2020) - Laidlaw, Rebecca A.; Gunnarsson, Tómas G.; Méndez, Verónica; Carneiro, Camilo; Þórisson, Böðvar; Wentworth, Adam; Gill, Jennifer A.; Alves, José A.
Abstract : Ground‐nesting species are vulnerable to a wide range of predators and often experience very high levels of nest predation. Strategies to reduce nest vulnerability can include concealing nests in vegetation and/or nesting in locations in which nests and eggs are camouflaged and less easy for predators to locate. These strategies could have important implications for the distribution of ground‐nesting species and the success rates of nests in areas with differing vegetation structure. However, the factors influencing the success of nest concealment and camouflage strategies in ground‐nesting species are complex. Here we explore the effects of local vegetation structure and extent of nest concealment on nest predation rates in a range of ground‐nesting, sympatric wader species with differing nest concealment strategies (open‐nest species: Oystercatcher Haematopus ostralegus, Golden Plover Pluvialis apricaria and Whimbrel Numenius phaeopus; concealed‐nest species: Black‐tailed Godwit Limosa limosa, Redshank Tringa totanus and Snipe Gallinago gallinago ) in south Iceland, in landscapes that comprise substantial variability in vegetation structure at a range of scales. We monitored 469 nests of these six wader species in 2015 and 2016 and 40% of these nests were predated. Nest predation rates were similar for open‐nest and concealed‐nest species and did not vary with vegetation structure in the surrounding landscape, but nest‐concealing species were 10% more likely to have nests predated when they were poorly concealed, and the frequency of poorly concealed nests was higher in colder conditions at the start of the breeding season. For concealed‐nest species, the reduced capacity to hide nests in colder conditions is likely to reflect low rates of vegetation growth in such conditions. The ongoing trend for warmer springs at subarctic latitudes could result in more rapid vegetation growth, with consequent increases in the success rates of early nests of concealed‐nest species. Temperature‐related effects on nest concealment from predators could thus be an important mechanism through which climate change affecting vegetation could have population‐level impacts on breeding birds at higher latitudes.